Design of a New Glass Cleaning Robot - Jiang, Haoyu (Journal of Theory and Practice of Engineering Science, 2024)
Improve the various abilities of glass cleaning robots, such as climbing ability and obstacle crossing ability at any angle, change the traditional movement mode of robots, and enable them to perform obstacle free movement in three-dimensional space. Taking inspiration from the quadruped movement of geckos, the UG software in mechanical CAD/CAM is used to simulate the structure of a glass cleaning robot for gait planning and structural design. By studying the force situation, the dimensions of the four bar mechanism and the size of the suction cup of the vacuum suction cup quadruped glass cleaning robot were derived. The structural design diagram was drawn, and its operating trajectory and mode were explained. Create post-processing through Postbuilder, conduct comprehensive testing and simulation to ensure accuracy before processing its components. The calculation shows that the thigh step distance within one cycle is 89.83 mm, and the calf step distance is 3.11 mm. So, the total step distance of a single leg in one cycle is 92.94 mm. Based on this, a top-down modeling approach was adopted, and assembly methods, connection methods, and driving methods were set in the simulation. The cosine function was used to control the motion trajectory of the legs. This design effectively simulates the motion of geckos. In future research, we will continue to focus on the dynamic trajectory of the robot's tail, in order to enable the robot to adjust its posture through its tail under microgravity and make the motion of the gecko like robot more flexible.